A Study of Emerging Trends & Challenges in Paints & Coatings Industry in India - Desai, Devang (Indian Journal of Marketing, 2011)
Indian Paints & Coatings industry was highly unorganized and fragmented before 1990s due to high excise duties levied on paints manufactured by organized sector players, making their products unaffordable. This was the period during which the unorganized sector flourished because of a substantial price difference between paints manufactured by the unorganized and organized players. In the 1990s, helped by a growing economy, the Indian paint industry recorded a healthy growth of 12-13% annually. This was mainly due to a drastic reduction in excise from a staggering 40% to 16%. Today, the Indian paint industry is a 11000 crores industry and is growing at the rate of more than 15% p.a. The Indian paint industry is divided into two main market segments-industrial and decorative paints. While industrial paints are used for protection against corrosion and rust on steel structures, vehicles, white goods and appliances, decorative paints are used in protecting valuable assets like buildings. As sophisticated technology is not a prime requisite for manufacturing decorative paints, the industry is flooded with a number of small players catering to the lower-end of the market by supplying low value unbranded products in small quantities. On the contrary, the share of the unorganized sector in the industrial paints segment is relatively limited. This is because technology is the overriding factor in this segment and industrial paints require constant upgradation and servicing. In the current research paper, an attempt has been made to understand the paint industry from its historic perspective and its situation in current economic conditions in India. The main purpose of the study is to understand the global and Indian paint industry scenario, various products and market segments, opportunities & challenges, and key success factors for the industry.